Opacity calculations in four to nine times ionized Pr, Nd, and Pm atoms for the spectral analysis of kilonovae. Issue 1 (4th November 2022) - Carvajal Gallego, H; Deprince, J; Berengut, J C; Palmeri, P; Quinet, P
ABSTRACT: New atomic data for radiative transitions in Pr V–X, Nd V–X, and Pm V–X were determined by means of large-scale calculations involving three independent theoretical methods, i.e. the pseudo-relativistic Hartree–Fock method including core-polarization corrections (HFR+CPOL), the multiconfiguration Dirac–Hartree–Fock (MCDHF) method, and the configuration interaction many-body perturbation theory (CI + MBPT) implemented in the ambit program. This multiplatform approach allowed us to estimate the reliability of the results obtained and to extract a large amount of energy levels, wavelengths, transition probabilities, and oscillator strengths for the determination of opacities required for the analysis of the spectra emitted in the early phases of kilonovae following neutron star mergers, i.e. for typical conditions corresponding to temperatures T > 20 000 K, a density ρ = 10 −10 g cm −3, and a time after the merger t = 0.1 d. Our radiative parameters were compared in detail with the few experimental data published so far and their impact on the calculated opacities, in terms of atomic computation strategy, was also examined.